Analysis of Production Trends of Mackerel Tuna (Euthynnus affinis) Landed at Nusantara Fishing Port of Brondong (NFP Brondong), Lamongan Regency, East Java, Indonesia - Audia Ramadani; Siti Maharani; Fadilah Auliah; Oktrin Syahrani; Muhammad Rafi; Sudirman Adibrata (Coastal and Marine Journal, 2025)
This study aimed to analyze the production trends and production value of mackerel tuna landed at Nusantara Fishing Port of Brondong (NFP Brondong), Lamongan Regency, East Java, within Indonesian Fisheries Management Area (IFMA) 712. The research was conducted from April to May 2025 using a quantitative descriptive approach based on time-series data from 2020 to 2024 obtained from the Statistical Data Portal of the Ministry of Marine Affairs and Fisheries of Indonesia. The results showed that mackerel tuna production exhibited a fluctuating pattern throughout the study period. The highest production was recorded in 2024 at 53.18 tons, while the lowest production occurred in 2022 at 18.37 tons, with an average annual production of 35.29 tons. The production value also fluctuated, reaching its highest level in 2023 at IDR 1,098,435,000 and its lowest level in 2024 at IDR 464,758,000. Fluctuations in production volume were likely influenced by fishing seasons, weather conditions, fishing activities, and oceanographic factors in the Java Sea. Meanwhile, fluctuations in production value were associated with market prices, consumer demand, and fish quality. The findings indicate that mackerel tuna remains an important fishery commodity in IFMA 712. Therefore, sustainable fisheries management is necessary through continuous production monitoring and appropriate control of fishing efforts to ensure resource sustainability and support fishers’ welfare.